2023
DOI: 10.1021/acs.jpcc.3c07027
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Evidence for Distorted Tetrahedral ≡Ti–OH Sites Supported on Amorphous Silica and Their Effect on the Adsorption of Polar Molecules

Branden E. Leonhardt,
Hengyuan Shen,
Martin Head-Gordon
et al.

Abstract: This study presents experimental and theoretical evidence for distorted �Ti−OH groups supported on amorphous SiO 2 and examines the influence of distortion on the strength of adsorption of polar molecules. For the theoretical part of this effort, we developed a model for isolated �Si−OH or �Ti−OH groups on the surface of amorphous silica. The �M−OH group is represented by a T8−11 cluster surrounded by a T747 cluster representing the surrounding amorphous silica. The properties of the small cluster are describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 74 publications
3
13
0
Order By: Relevance
“…We have recently reported that a small fraction (<15%) of silica-supported Ti–OH sites are heavily distorted. In comparison, the remaining 85% have structures consistent with those derived from analysis of EXAFS data . These conclusions were drawn from a combination of experimental and theoretical studies of pyridine adsorption on silica-supported Ti–OH sites.…”
Section: Introductionsupporting
confidence: 53%
See 4 more Smart Citations
“…We have recently reported that a small fraction (<15%) of silica-supported Ti–OH sites are heavily distorted. In comparison, the remaining 85% have structures consistent with those derived from analysis of EXAFS data . These conclusions were drawn from a combination of experimental and theoretical studies of pyridine adsorption on silica-supported Ti–OH sites.…”
Section: Introductionsupporting
confidence: 53%
“…The straddled geometry is more favorable for facet areas less than 3.925 Å 2 , whereas the in-plane geometry is more favorable above this value. Since most Ti–OH sites in Ti/SiO 2 exhibit facet areas smaller than 3.925 Å 2 , the straddled configuration is likely the more common one . However, the minority of in-plane transition states for facets larger than 3.925 Å 2 are relatively stable.…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations